대목 종류 및 이중접목이 시설수박의 품질과 시들음증 발생에 미치는 영향 - 권준국(Joon-Kook Kwon); 권기범(Gi-Bum Kweon); 강경희(Kyung-Hee Kang); 최영하(Young-Hah Choi); 강남준(Nam-Jun Kang); 이재한(Jae-Han Lee); 정호정(Ho-Jeong Jeong); 박진면(Jin-Myeon Park) (Weon'ye gwahag gi'sulji, 2005)
대목의 종류가 시설수박의 품질 및 시들음증 발생에 미치는 영향을 구명하고자, 겨울철 저온기에 시설수박 주산지인 함안지역의 시들음증이 상습적으로 발생되는 포장에서 참박, 신토좌, 안동오이, 이중대목(원대목: 신토좌, 중간대목: 참박) 등에 대해 생육 및 과실 특성, 식미도, 시들음증 발생정도를 평가하였다. 수박의 전반적인 생육과 과실의 발육은 참박에 접목한 것에 비해 안동오이, 신토좌, 이중대목에 접목한 것이 왕성하였다. 그러나 과실 당도, 과피 두께, 식미도 등의 과실 품질은 참박에 접목한 수박이 신토좌, 안동오이, 이중대목 등에 접목한 수박이 우수하였다. 시들음증은 참박 대목에 접목한 것이 가장 심하게 발생하였고 신토좌나 이중대목에 접목한 것은 매우 낮은 발생률을 나타내었다. 따라서 시들음증이 발생이 심한 포장은 신토좌, 이중대목, 안동오이 등의 대목으로 교체함으로써 발생을 줄일 수 있다. To investigate the effect of rootstocks and double grafting on the fruit quality and withering occurrence of greenhouse watermelon (Citrullus vulgaris S.), three rootstocks, Chambak (Lagenaria vulgaris), Shintozwa (C. maxima × C. moschata), Andongoi (Sicyos angulatus L.), and double grafting using Shintozwa as primary rootstock and Chambak as secondary rootstock, were evaluated. The parameters used were withering occurrence, plant growth and fruit quality during low temperature season at annually withering field of a major producing district, Haman. Remarkable withering symptoms were observed in plants grafted onto Chambak but very low occurrence showed in plants grafted onto Shintozwa and double grafted. Watermelon plants grafted onto rootstocks such as Andongoi, Shintozwa, and double grafted showed comparable shoot growth and fruit development as compared to the those grafted onto popular rootstock, Chambak. However, the soluble solids contents, rind thickness, and flavour of watermelons grafted onto Chambak was superior as compared to the those grafted onto the other rootstocks. The results also showed that changes of rootstocks from popular rootstock, Chambak, to Shintozwa, double-grafted and Andongoi rootstock could be alternative method to reduce the withering occurrence under greenhouse cultivation during low temperature season. KCI Citation Count: 4